Evaluation of factors contributing to adoption of management practices productivity and net income in shrimp farming in Gujarat, India - Ponnusamy, Kuppusamy; Pillai, Subramaniyam Mathusudananan (Indian Journal of Fisheries, 2014)
A study was conducted to identify the factors contributing to productivity and net income of shrimp farming in four districts of south Gujarat by randomly interviewing 129 shrimp farmers. The variables were identified hypothetically to arrive at the relationship between factors affecting the adoption of management practices, productivity and net income in shrimp farming. The data was analysed using analysis of variance (ANOVA), Pearson’s correlation coefficients and multinomial logistic regression analysis. The fit of logistic regression was good for adoption and productivity. Cox and Snell pseudo R2 for adoption and productivity were 32 and 42%, respectively. For adoption, likelihood ratio of education, social participation and use of own credit were significant. Use of own credit is the only factor responsible for a shift between low and high adoption score categories. The model predicted correct group of adoption score in only 61% of the cases with poor fit observed in high adoption score category. The results of the study indicate that higher productivity is possible only through infusing large credit flow and motivation to adopt better management practices.